Medicinal Plants of the Family Lamiaceae in Pain Therapy: A Review. (8th May 2018) - Uritu, Cristina M.; Mihai, Cosmin T.; Stanciu, Gabriela-Dumitrita; Dodi, Gianina; Alexa-Stratulat, Teodora; Luca, Andrei; Leon-Constantin, Maria-Magdalena; Stefanescu, Raluca; Bild, Veronica; Melnic, Silvia; Tamba, Bogdan I.
Abstract : Recently, numerous side effects of synthetic drugs have lead to using medicinal plants as a reliable source of new therapy. Pain is a global public health problem with a high impact on life quality and a huge economic implication, becoming one of the most important enemies in modern medicine. The medicinal use of plants as analgesic or antinociceptive drugs in traditional therapy is estimated to be about 80% of the world population. The Lamiaceae family, one of the most important herbal families, incorporates a wide variety of plants with biological and medical applications. In this study, the analgesic activity, possible active compounds of Lamiaceae genus, and also the possible mechanism of actions of these plants are presented. The data highlighted in this review paper provide valuable scientific information for the specific implications of Lamiaceae plants in pain modulation that might be used for isolation of potentially active compounds from some of these medicinal plants in future and formulation of commercial therapeutic agents.